P125 A primary care audit on asthma patients with frequent exacerbations and the potential impact of national review of asthma deaths (NRAD) recommendations. (15th November 2016) - Chaudhuri, R; Thomson, NC; McCallum, C; O'Pray, H; Barclay, ST; Murray, D; MacBride-Stewart, S; Sharma, V; Shepherd, M; Lee, WT
Abstract : Background: One of the key recommendations of NRAD 1 is that patients who require 2 courses or more of oral corticosteroids (OCS) for asthma in the last 12 months should be referred to a specialist asthma service. This may put undue pressure on secondary care asthma services as the number of such patients is unknown. Aims: To identify asthma patients with recurrent exacerbations who would merit referral to secondary care, and to study the biopsychosocial factors associated with frequent exacerbations. Methods: Data were retrospectively collected on asthma patients aged >18 years from 10 primary care practices in the North Glasgow area over a 12-month period between 2014 and 2015. All prescriptions patients received in primary care were obtained. Only patients who received asthma treatment in the last 12 months were included. Patients were identified as a 'frequent exacerbator' if they had received ≥2 courses of OCS for asthma, and a "short-acting beta 2-agonist (SABA) over-user" if they had required >12 SABA inhalers in the last 12 months. Results: Out of 2639 asthma patients studied, 7% were frequent exacerbators, 5% were SABA over-users, 1% were both. Compared with all asthma patients, frequent exacerbators were older (mean age 58 ± 16 vs 48 ± 17) and more likely to be female (68% vs 58%). They had a higher prevalence of cigarette exposure and multiple co-morbidities including COPD, gastro-oesophageal reflux, anxiety, depression, rhinitis and osteoporosis. 41% of frequent exacerbators did not have an asthma review in primary care in the last 12 months and 42% had no previous input from secondary care. The total number of patients who would merit referral to a specialist asthma service from the 10 primary care practices was 78 over a 12-month period. Conclusions: Frequent exacerbators and SABA over-users account for a small proportion of asthma patients attending primary care. The number of new referrals generated by the NRAD recommendation may put additional pressure on secondary care asthma services. Funder: supported by an educational grant from Novartis Pharmaceuticals. Reference: Levy ML. The national review of asthma deaths: what did we learn and what needs to change? Breathe (Sheff ) 2015;11 (1):14–24.